PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KINERJA ORGANISASI DI BALAI BESAR PASCAPANEN KEMENTERIAN PERTANIAN - Abdul Rifan; Ginung Pratidina; Euis Salbiah (LPPM Universitas Djuanda Bogor, 2019)
This research is aimed at analyzing the influence of implementation of government internal control system on the organizational performance in Post-Harvest Agency, Ministry of Agriculture. The government internal control system is measured on five dimensions, namely control environment, risk evaluation, control activity, information and communication, and monitoring. The the organizational performance is measured on five dimensions, namely productivity, service quality, responsivity, responsibility, and accountability. This research uses the analytical-quantitative method. The samples of this research are drawn 58 respondents from 137 civil servants in Post-Harvest Agency. The data of this research is collected by using observation, interview, and questionnaire. The data is statistically analyzed by using Weight Mean Score, Spearman Rank Correlation, and Coefficient Determination. The results of this research indicate three findings. Firstly, the analysis by Weight Mean Score indicates the mean score of implementation of government internal control system 4.09, categorized as good and the mean score of organizational performance 4.19, categorized as good. Secondly, the analysis by Rank Spearman Correlation gains the coefficient correlation 0.566 that has a middle relationship of implementation of government internal control system to organizational performance. Thirdly, the analysis by Coefficient Determination indicates that the influence of implementation of government internal control system contributes to organizational performance 32.0%.Keywords: Organizational Performance, Monitoring and Evaluation, Government Internal Control System.